Gut microbiota-derived metabolites mediate the protective effects of Poria cocos polysaccharide derivatives against oxidative stress - Chunmin Yang; Fenfa Li; Pingping Yan; Xichun Peng (Food Bioscience, 2026)

NS1-A53D enhances HA stability to coordinate viral entry with vRNP export and replication during adaptation of H1N1 canine influenza virus - Min Zhu; Rang Wang; Xiaolong Li; Yefan Zhou; Linying Peng; Pingping Wang; Huabo Zhou; Jianni Huang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

Dietary supplementation of Radix Isatidis polysaccharides improves meat quality in broilers by regulating lipid metabolism, antioxidant defense, and the gut-muscle axis - Wei Wang; Wenbin Ouyang; Haibo Xiao; Panpan Shi; Pingping Li; Jianguo Zeng; Meirong Song; Sundus Javed; Peng Huang (Research in Veterinary Science, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Bioactive electrospun membrane with DHBA/Zn-MOF for enhancing neurovascular coupling in diabetic wound healing - Manjuan Li; Peng Hua; Linsa Zhou; Lexuan Fang; Pingping Ma; Zixuan Wang; Shicui Jiang; Qiang Zhou; Gaowen Li; Xudong Zheng; Chi Zhang; Litai Jin; et al. (Chemical Engineering Journal, 2026)

Sediment-associated Rare Earth Elements in an Urban River: Bioavailability and Ecological Risks to Aquatic Biota - Ruijie Peng; Pingping Wu; Zhilin Chen; Junzhuo Cai; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Processes, 2026)

Multi-component catalysts with three-dimensional porous structures for exhaust gas purification: Activity for soot and CO - Xiaolong Sheng; Li Li; Changcheng Fu; Peng Zhang; Lefu Yang; Mingzhang Pan; Jinkai Gu; Pingping Huang; Yupei Yang; Tian Zhang; Wei Guan (Journal of Environmental Chemical Engineering, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Effects of nitrogen, phosphorus, iron, and silicon on the growth, total lipid content, and fatty acid composition of the diatom Corethron sp. - Maoyingzang Peng; Pingping Liu; Ruibing Peng; Xiamin Jiang; Sheng Li; Maowang Jiang (Journal of Applied Phycology, 2026)

The impact of anti-gout medications on eight cardiovascular diseases: a Mendelian randomized study - Pingping Peng; Jingting Wang; Miaozhen Huang; Congting Hu; Suyan Liu; Jia Liu; Jiaqin Cai; Xiaoxia Wei; Hong Sun (European Journal of Clinical Pharmacology, 2026)

Hydrological response to climate change and urbanization in a semi-arid urban river - Jiqiang Lyu; Yan Wang; Kexin Wang; Wenya Liu; Dongyong Sun; Pingping Luo; Zhaohui Zhou; Meng Jiao; Aidi Huo; Peng Guo (Urban Climate, 2025)

Curcumin alleviates ovarian hyperstimulation syndrome in the rat model via inhibiting the nuclear factor kappa B/hypoxia-inducible factor-1α signaling pathway - Lilan Sun; Xiumei Zhuo; Dandan Qi; Hao Ma; Fanhua Kong; Pingping Sun; Yan Zhang; Peng Xue; Huagang Ma (Histochemistry and Cell Biology, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Selective breeding boosts oyster resilience to ocean acidification via energy budget modulation - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Food-derived peptides as novel therapeutic strategies for NLRP3 inflammasome-related diseases: a systematic review - Ziqi Zhang; Yuan Zhang; Meiying Zhang; Chenfeng Yu; Pingping Yang; Minxuan Xu; Jitao Ling; Yuting Wu; Zicheng Zhu; Yixuan Chen; Ao Shi; Xiao Liu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Corrigendum to “Physiological energetics of selectively bred oysters (Crassostrea hongkongensis) under marine heatwaves” [Mar. Environ. Res. 204 (2025) 106871] - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Physiological energetics of selectively bred oysters (Crassostrea hongkongensis) under marine heatwaves - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

An efficient, robust, and affordable photothermal membrane using polyvinyl alcohol encapsulated MXene/non-woven fibers for solar desalination/sewage purification - Ye Cao; Pingping Gong; Peng Yu; Yijing Wang; Zhenli Zuo; Changyuan Pan; Xinbing Wang; Peng Zhong; Xiaohua Ma (Chemical Engineering Journal, 2025)

Controlled oxidative decomposition of rice husk to induce formation of hierarchically meso-macroporous carbon foams with unprecedented porosity - Hao Wu; Jun Yang; Ge Yang; Pingping Wu; Wei Xing; Peng Bai; Zifeng Yan (Biomass and Bioenergy, 2025)

Exploring the environmental influences and community assembly processes of bacterioplankton in a subtropical coastal system: Insights from the Beibu Gulf in China - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Yusen Li; Wenjian Chen; Zelong Zhao; Linyuan Jiang; Lei Zhou (Environmental Research, 2024)

Alumina lattice confined Niσ+ species as highly selective and anti-coking sites for sustainable propane dehydrogenation - Peng Bai; Zhenxiang Zhao; Tian Nan; Jun Yang; Yantao Xue; Chunlin Wang; Shuanghui Lu; Hao Wu; Guoming Wang; Ziyi Zhong; Pingping Wu; Chunzheng Wang; et al. (Chemical Engineering Journal, 2024)

Unravelling the structure-performance relationship of zeolite Beta in the catalytic cracking of low-density polyethylene by proposing gasoline factor as the descriptor - Yi Wang; Hao Wu; Yuanhao Liu; Wansheng Wang; Pingping Wu; Hongchao Fan; Zhihui Liu; Peng Bai; Zifeng Yan (Fuel, 2024)

Seasonal dynamics of antibiotic resistance genes and mobile genetic elements in a subtropical coastal ecosystem: Implications for environmental health risks - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Wei Li; Yusi Zheng; Yusen Li; et al. (Environmental Research, 2024)

Evolution of an arid social-ecosystem with different water utilization spanning 12,000 years - Aidi Huo; Zhixin Zhao; Pingping Luo; Qi Liu; Qiangbing Huang; Zhenhong Wang; Jianbing Peng (Journal of Cleaner Production, 2024)

Analyte-perturbed balance between reducibility and fluorescence of Ti3C2 MXene quantum dots for label-free, dual-mode detection of silver ions - Peng Jin; Pingping Wan; Chunyan Zhang; Xu Li; Yan Wang; Jianxin Luo; Kun Li (Analytica Chimica Acta, 2024)

N-S variations of crustal structure beneath the central Tarim Basin from joint inversion of receiver functions, ambient seismic noise surface wave dispersion, and magnetotelluric data - Miao Peng; Handong Tan; Changhong Lin; Shaoqian Hu; Pingping Wu; Lehong Xu; Chonglong Wang; Yifan Liu; Lihui Wang; Bohao Li (Tectonophysics, 2024)

The relationship between maternal exposure to ambient air pollutants and premature rupture of membranes: A systematic review and meta-analysis - Yaxin Liang; Min Li; Qiubo Lyu; Pingping Li; Yuhan Lyu; Yue Yu; Wuqiang Peng (Environmental Pollution, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

Discussion on the development of offshore floating photovoltaic plants, emphasizing marine environmental protection - Sheng Wu; Nian Jiang; Shuai Zhang; Pingping Zhang; Peng Zhao; Yang Liu; Yanhui Wang (Frontiers in Marine Science, 2024)
The development of solar energy is one of the most effective means to deal with the environmental and energy crisis. The floating photovoltaic (PV) system is an attractive type because of its multiple advantages and has been well developed based on fresh water areas on land. This paper focuses on the expansion of this sector towards the ocean, offshore floating PV plants, which is the new growth point with huge potential for the future PV sector. For this new field, the technology readiness level is really low and research to understand the interaction between offshore floating PV plants and marine environment are proceeding. In this paper, we aim to discuss the technological feasibility of offshore floating PV plants as well as analyze potential impacts on the marine environment during the life cycle of PV from manufacturing until disposal.

Magnetically separable Co0.6Fe2.4O4/MIL-101-NH2 adsorbent for Congo red efficient removal - Zhenhong Zhang; Yuye Zhong; Peng Sun; Pingping Zhao; Houbin Li; Xinghai Liu (Environmental Science and Pollution Research, 2024)

Effects of dietary supplementation with Radix Isatidis polysaccharide on egg quality, immune function, and intestinal health in hens - Panpan Shi; Zenghao Yan; Miaofen Chen; Pingping Li; Deqin Wang; Junjuan Zhou; Zhaojie Wang; Shihao Yang; Zhikun Zhang; Chuyuan Li; Yulong Yin; Peng Huang (Research in Veterinary Science, 2024)

Quantitative assessment of spatiotemporal dynamics in vegetation NPP, NEP and carbon sink capacity in the Weihe River Basin from 2001 to 2020 - Jiqiang Lyu; Xianghang Fu; Chen Lu; Yueyan Zhang; Pingping Luo; Peng Guo; Aidi Huo; Meimei Zhou (Journal of Cleaner Production, 2023)

Dissecting the genetic basis of grain weight and size in common oat by genome-wide association study - Honghai Yan; Di Deng; Pingping Zhou; Yun Peng; Xiaolong Dong; Shuchang Li; Yongjie Zhang; Qin Man; Ziqin Lv; Tao Chen; Changzhong Ren; Yuanying Peng (Journal of Cereal Science, 2023)

Experimental study on slope morphological characteristics and stability analysis of GCHP engineering in the loess plateau - Zhixin Zhao; Aidi Huo; Yuxiang Cheng; Pingping Luo; Jianbing Peng; Ahmed Elbeltagi; Mohamed EL-Sayed Abuarab; Ali Mokhtar (Advances in Space Research, 2023)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

Identification and Characterization of microRNAs in the Gonads of Litopenaeus vannamei Using High-Throughput Sequencing - Wei Li; Pingping He; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Li Zhang; Bin Zhang; Yusi Zheng; Xin Li; Qingsong He; Longcheng Liu; Chang Yuan; et al. (Fishes, 2022)
Although the expression of miRNAs has been widely applied to investigate on gonads, the role of miRNAs in the gonadal development of white Pacific shrimp (Litopenaeus vannamei) remains unknown. In this study, we performed high-throughput sequencing to identify the sex-related microRNAs (miRNAs) that elucidated the regulatory mechanisms on the gonadal differentiation of L. vannamei. We obtained a total of 29,671,557 and 28,526,942 raw reads from the ovaries and testes library, respectively. We then mapped 26,365,828 (92.73%) of the ovarian clean sequences and 23,694,294 (85.65%) of the testicular clean sequences for a transcriptome reference sequence of L. vannamei. After blasting the miRNA sequences against the miRBase database, we identified 153 significantly differentially expressed miRNAs between the ovaries and testes. To confirm the high-throughput sequencing results, we used a reverse transcriptase–quantitative polymerase chain reaction (RT-qPCR) to verify the expression patterns of the seven most differentially expressed miRNAs (i.e., novel_mir23, miR-92b-3p_3, miR-12-5p_2, novel_mir67, miR-279_1, let-7-5p_6, miR-263a-5p_1). According to the results of RT-qPCR, most of the miRNAs were expressed consistently with the high-throughput sequencing results. In addition, the target genes significantly enriched several Kyoto Encyclopedia of Genes and Genome (KEGG) pathways that were closely related to gonadal differentiation and development, including extracellular matrix–receptor interaction, Hedgehog signaling pathway, protein digestion and absorption and cell adhesion molecules (CAMs). This study revealed the first miRNAs sequencing of L. vannamei gonads. We identified sex-related differentially expressed miRNAs and KEGG pathways, which will be helpful to facilitate future research into the regulatory mechanism on the gonadal differentiation of L. vannamei.

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Effects of air pollution on physiological traits of Ligustrum lucidum Ait. leaves in Luoyang, China - Xiping Zhao; Pingping Guo; Yongqiang Yang; Haixin Peng (Environmental Monitoring and Assessment, 2021)

Functional Differences Between Two Kv1.1 RNA Editing Isoforms: a Comparative Study on Neuronal Overexpression in Mouse Prefrontal Cortex - Liting Zhang; Zetong Peng; Wenjun Bian; Pingping Zhu; Bin Tang; Wei-Ping Liao; Tao Su (Molecular Neurobiology, 2021)

Genetic diversity and genome-wide association analysis in Chinese hulless oat germplasm - Honghai Yan; Pingping Zhou; Yun Peng; Wubishet A. Bekele; Changzhong Ren; Nicholas A. Tinker; Yuanying Peng (Theoretical and Applied Genetics, 2020)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Use of multiple isotopes to evaluate the impact of mariculture on nutrient dynamics in coastal groundwater - Kang Pingping; Liu Peng; Wang Fuqiang (Environmental Science and Pollution Research, 2019)

Joint Inversion of 1-D Magnetotelluric and Surface-Wave Dispersion Data with an Improved Multi-Objective Genetic Algorithm and Application to the Data of the Longmenshan Fault Zone - Pingping Wu; Handong Tan; Miao Peng; Huan Ma; Mao Wang (Pure and Applied Geophysics, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

Development of genic SSR markers from an assembled Saccharina japonica genome - Jie Peng; Linan Zhang; Xiaojie Li; Cuiju Cui; Ruina Wu; Pingping Tian; Yan Li; Yanling Liu (Journal of Applied Phycology, 2016)

Transcriptomic Analyses Reveal Novel Genes with Sexually Dimorphic Expression in Yellow Catfish (Pelteobagrus fulvidraco) Brain - Jianguo Lu; Min Zheng; Jiajia Zheng; Jian Liu; Yongzhuang Liu; Lina Peng; Pingping Wang; Xiaofeng Zhang; Qiushi Wang; Peixian Luan; Shahid Mahbooband; Xiaowen Sun (Marine Biotechnology, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Development of 27 trinucleotide microsatellite markers for Saccharina japonica using next generation sequencing technology - Linan Zhang; Jie Peng; Xiaojie Li; Yanling Liu; Cuiju Cui; Hao Wu; Ruina Wu; Pingping Tian; Yan Li (Conservation Genetics Resources, 2014)